Generalized model of random successive pulses industrial radio interference in the workhalls industrial enterprises - Полтавский, Константин Николаевич; Сидоров, Геннадий Иванович (Eastern-European Journal of Enterprise Technologies, 2012)
Investigation of statistical radio signals characteristic and radio interferences is necessary to design industrial wireless modems. Since inner radio interferences in armored concrete workhalls is close to zero, it is necessary to analyze only individual radio interferences that influence on radio receiver device. In given work was investigated amplitude of a chaotic pulse sequence of industrial interferences with random occurrence by Poisson low. It is assumed that duration of occurrence and amplitude is random. Current spectrum of chaotic sequence is found with the main theorem of spectra. It was found mathematic expectation of spectrum with exponential distribution of the interval between pulses appearance. It is proved that the cumulative effect of chaotic sequence of overlapping pulses RFI that influenced to radio receiver describes by log-normal low